Great expectations: assessing the impact of commercialization-focused policies among Malaysia’s public research institutes - Strong, Derek Ryan; Chandran, V.G.R.; Hayter, Christopher S. (Taylor & Francis, 2018)
In 2006, the Malaysian government released its 9th five-year development plan which, among other things, directed the country’s numerous public research institutes (PRIs) to focus primarily on commercializing technologies stemming from their respective research agendas. This directive envisioned a de facto division of labor between universities, that would emphasize basic research, and PRIs, that would become Malaysia’s translational research and technology commercialization hubs. Employing a scientific and technical human capital conceptual lens, this paper assesses the extent to which PRIs have met the expectations of the new commercialization directive through the analysis of data collected during a 2011–2012 survey among university and PRI researchers. First, we find descriptively that, in comparison to university researchers, PRI researchers do not differ substantially in terms of average patents and prototypes produced, our proxies for technology commercialization. Second, we investigate factors among PRI researchers that explain commercialization behavior and find that holding a PhD correlates strongly with publication and patenting behavior while conducting applied research and expressing adequate commercialization support correlates modestly with prototyping behavior. Implications for research and policy are discussed.